Single Particle Tracking of ADAMTS13 (A Disintegrin and Metalloprotease with Thrombospondin Type-1 Repeats) Molecules on Endothelial von Willebrand Factor Strings - De Ceunynck, Karen (American Society for Biochemistry and Molecular Biology, 2014)
von Willebrand factor (VWF) strings are removed from the endothelial surface by ADAMTS13 (a disintegrin and metalloprotease with thrombospondin type-1 repeats)-mediated proteolysis. To visualize how single ADAMTS13 molecules bind to these long strings, we built a customized single molecule fluorescence microscope and developed single particle tracking software. Extensive analysis of over 6,000 single inactive ADAMTS13(E225Q) enzymes demonstrated that 20% of these molecules could be detected in at least two consecutive 60-ms frames and followed two types of trajectories. ADAMTS13(E225Q) molecules either decelerated in the vicinity of VWF strings, whereas sometimes making brief contact with the VWF string before disappearing again, or readily bound to the VWF strings and this for 120 ms or longer. These interactions were observed at several sites along the strings. Control experiments using an IgG protein revealed that only the second type of trajectory reflected a specific interaction of ADAMTS13 with the VWF string. In conclusion, we developed a dedicated single molecule fluorescence microscope for detecting single ADAMTS13 molecules (nm scale) on their long, flow-stretched VWF substrates (μm scale) anchored on living cells. Comprehensive analysis of all detected enzymes showed a random interaction mechanism for ADAMTS13 with many available binding sites on the VWF strings.